2004
DOI: 10.1073/pnas.0407557101
|View full text |Cite
|
Sign up to set email alerts
|

α,β hybrid peptides: A polypeptide helix with a central segment containing two consecutive β-amino acid residues

Abstract: Conformational studies on the synthetic 11-aa peptide t-butoxycarbonyl (Boc)-Val-Ala-Phe-␣-aminoisobutyric acid (Aib)-(R)-␤ 3 -homovaline (␤Val)-(S)-␤ 3 -homophenylalanine (␤Phe)-Aib-Val-AlaPhe-Aib-methyl ester (OMe) (peptide 1; ␤Val and ␤Phe are ␤ amino acids generated by homologation of the corresponding L-residues) establish that insertion of two consecutive ␤ residues into a polypeptide helix can be accomplished without significant structural distortion. Crystal-structure analysis reveals a continuous heli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
43
0

Year Published

2007
2007
2012
2012

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 56 publications
(43 citation statements)
references
References 13 publications
(9 reference statements)
0
43
0
Order By: Relevance
“…Past work on the folding behavior of peptides and proteins indicates that limited backbone modification in a given sequence, including replacement of one or two ␣-residues with ␤-residues, can be accomplished without significantly altering native structure or function (11)(12)(13). More recently, we have shown that a particular type of nonnatural backbone, composed of a mixture of ␣-and ␤-amino acid residues in an ␣␣␤␣␣␣␤ pattern, can partially mimic the folding and self-assembly behavior of parent ␣-peptide side-chain sequences (14,15).…”
mentioning
confidence: 99%
“…Past work on the folding behavior of peptides and proteins indicates that limited backbone modification in a given sequence, including replacement of one or two ␣-residues with ␤-residues, can be accomplished without significantly altering native structure or function (11)(12)(13). More recently, we have shown that a particular type of nonnatural backbone, composed of a mixture of ␣-and ␤-amino acid residues in an ␣␣␤␣␣␣␤ pattern, can partially mimic the folding and self-assembly behavior of parent ␣-peptide side-chain sequences (14,15).…”
mentioning
confidence: 99%
“…The positive ion ESI mass spectra of all these peptides (1)(2)(3)(4)(5)(6)(7)(8)(9)(10)(11)(12)(13)(14)(15)(16)(17)(18)(19)(20) + ions (Scheme 2). Fragmentation of these peptides can be explained by using the nomenclature, which was originally proposed for α-peptides by Roepstorff and Fohlman, and later modified by Biemann [18][19][20].…”
Section: Resultsmentioning
confidence: 99%
“…All the dipeptides were eluted from the column with the mobile phase ratio of 2:98 (CH 3 OH:CHCl 3 ) except for the dipeptides 5 and 6, which were eluted with the mobile phase ratio of 3:7 (hexane:ethyl acetate). The tetra-and hexapeptides were eluted from the column with the mobile phase ratio of 4:96 (CH 3 OH: CHCl 3 ) , 6:94 (CH 3 OH:CHCl 3 ), respectively.…”
Section: Synthesis Of the Peptidesmentioning
confidence: 99%
See 1 more Smart Citation
“…This strategy relied on the previously observed tolerance of protein secondary-structure to incorporation of β-amino acids [64][65][66][67], which were substituted into the primary sequence of GCN4-p1 and GCN4-pLI [68] (9 of the 33 residues) at positions distal to the interacting interface to avoid destabilizing the dimer or tetramer interface, respectively. The peptide based on GCN4-p1 associated as a trimer via x-ray crystallography, but was monomeric at concentrations sampled via analytical ultracentrifugation (AUC), whereas the α/β-version of GCN4-pLI associated as a trimer by AUC and a tetramer by x-ray crystallography (Figures 3e and f) [57•].…”
Section: Mixed α/β-Peptidesmentioning
confidence: 99%